PENEKANAN IDE POKOK DALAM PENGGUNAAN KALIMAT EFEKTIFPADA MAHASISWA PENDIDIKAN AKUNTANSI KELAS A REGULER 2013 - Halimatussakdiah Halimatussakdiah; Justhin Andrew A. S (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
The study objective was to determine whether accounting education student classA regular 2013 canunderstand and recognize effective sentences, particularly in the use of force or emphasis in a sentenceeffectively.The method used is descriptive qualitative method , the research procedure that usesdescriptive data in the form of words-written or spoken words of people-men and actors can beobserved. In this case, the authors use a questionnaire to assist in the research.The results achieved arestill many students that accounting education class A regular 2013 that do not understand the sentenceeffective, especially how to recognize an emphasis on effective sentence.The conclusions obtained fromthis research is that there are many students who do not understand the use of effective sentence. Thatstudents who do not understandthe sentence to understand the material effective, learning should bedone again on the matter.